Glutathione S-transferase in mediating adaptive responses of oats (Avena sativa) to osmotic and cadmium stress: genome-wide analysis - Chenbiao Xu; Lyu Jiang; Aixue Li; Jie Meng; Ping Yun; Jianfang Li; Changbin Liu; Yang Chen; Han Zhang; Hassan Ahmed Ibraheem Ahmed; Quan Gao; Lana Shabala; et al. (BMC Plant Biology)
Abstract Background Glutathione S-transferases (GSTs) are essential multifunctional enzymes. In the face of abiotic stresses such as drought and heavy metal exposure, plants utilize GSTs for detoxification and antioxidant defense, as these enzymes facilitate the conjugation of glutathione (GSH) with toxic compounds. Specific details of this process, however, remain unknown. Results This study identified 118 Avena sativa GST (AsGST) genes within the A. sativa genome and classified them into five subfamilies: Tau, Phi, Zeta, Lambda, and EF1Bγ. Phylogenetic analysis revealed that AsGSTs exhibit significant similarity to corresponding GST categories in Arabidopsis thaliana and Oryza sativa, indicating a possible common ancestor. Gene structure and conserved motif analysis demonstrated that AsGST genes within the same subfamily shares similarities in the number and positioning of exons and introns, as well as in motif composition, suggesting that these genes may perform analogous biological functions in A. sativa. The promoter regions of the identified genes are enriched with various cis-acting elements that play roles in plant growth and development, stress response, and hormone signaling. Transcriptomic analysis and real-time quantitative PCR (RT-qPCR) validation indicated that the expression of four AsGST genes (AsGSTU12, AsGSTU13, AsGSTU14, and AsGSTU15) was significantly up-regulated in the roots of A. sativa under both PEG-induced drought stress and CdCl2-induced cadmium stress. These genes likely regulate reactive oxygen species (ROS) levels by catalyzing their scavenging through glutathione (GSH) substrates, and may also participate in ABA signaling and the maintenance of osmotic homeostasis. Under cadmium stress, these genes may mitigate cadmium toxicity by enhancing the chelation and sequestration of cadmium via GSH or through its compartmentalization, as evident from the subcellular localization studies. Conclusion This study systematically described the GST gene family in A. sativa, characterized its expression patterns and potential functions in response to drought and cadmium stress, and confirmed the essential role of the AsGST gene family in mediating stress responses. The findings enhance our understanding of the mechanisms underlying stress tolerance and offer valuable genetic resources for breeding stress-tolerant A. sativa. The work also provides a theoretical framework and identifies gene targets for the development of stress-resistant A. sativa varieties.